Criticizing the Schools, Then and Now - Levin, Benjamin (Education Policy Analysis Archives, 1998)
Schools in many countries are facing intense and elevated levels of criticism, with much debate over whether the criticism is merited. Much of the criticism embodies a view that things used to be better years ago, when schools were not prey to the many defects they are alleged to show today. Recollections of the past may hide a mixed reality. In this article, criticisms of education from 1957 are compared with contemporary criticisms. Some issues have remained important across forty years, while a few new issues have emerged. Criticisms of forty years ago centered on the dominance of "professional educationists," progressivism, the life adjustment movement, the waning "spirit of competition," lax discipline, the lack of emphasis on classical and modern foreign languages, avoidance of science and math, the neglect of gifted children, the lack of training of children in moral and spiritual values, and low academic standards. Today's debates introduce the alleged test score declines, poor performance on international achievement comparisons, the supposed enormous increase in funding without positive results, the problem of high dropout rates, and the need to connect schooling and work. In addition, modern critics point to economic concerns, whether in terms of funding for education or in regard to the contribution of schooling to economic development.